Study on the use of commercial vegetable oils as green solvents in synthesis of 2-methyl-4(1H)-quinolin-4-ones - Thanh, Nguyen Dinh; Duan, Le The; Van, Tran Thi Thanh; Chi, Pham Mai; Quy, Luu Son; Anh, Pham Thi; Hien, Dang Thi Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: